The Impact Of Street Begging On The Movement And Safety Of Pedestrians: The Case Of Megenagna, Addis Ababa - Fana, Berhane (ASTU, 2024)
Begging On The Street Sidewalks Of Urban Centers Is One Of The Age-Old Activities And Possibly Occupations Of Society's Most Vulnerable Members, Particularly In Developing Countries. Even If Sidewalks Are The Vital Components Of Urban Infrastructure Designed To Facilitate Safe Pedestrian Movement, Street Begging Has Grown To Be A Serious Problem In Many Cities Weakening Pedestrian Safety And Mobility. This Research Investigated The Impact Of Street Begging On The Movement And Safety Of Pedestrians On The Sidewalks Of Addis Ababa, Particularly Atmegenagna Corridors. The Study Used Both Quantitative And Qualitative Data Types Where Surveys And Questionnaires Were Used To Identify Safety Concerns And Observations Were Conducted To Record The Time-Delayed, And Movement Patterns Of Street Begging Incidents. Descriptive And Statistical Analysis Techniques Were Used To Examine Pedestrian Movement Patterns Influenced By Street Beggars, Utilizing MS Excel For Data Visualization, And Hcmmodeling For Scoring Congestion Levels. The Result Of The Study Showed How Street Begging In Fluenced Movements In Four Sidewalk Segments, The Under Bridge Sidewalk Of The Roundabout, The Bridge Sidewalk, And The Road Leading To Shola And Bole, With Their Designated Names As A,B, C, And D Respectively. It Reveals Decreased Walking Speeds And Significant Lateral Shifts Inresponse To Begging Interventions Across All Segments, Particularly At Segment C, Where Thewider Lateral Positions Of 1.72 Meters Raise Concerns About Pedestrian Safety. Regardingcongestion, Segment A Maintained Moderate Congestion (Grade C With A Score Of 8.66),Segment B Slightly Increased (Grade D,10.7), Segment C Significantly Rose (Grade E,15.3), Andsegment D Minimally Changed. Predominant Concerns Of Safety Included Physical Safety,Environmental Cleanliness, Emotional Well-Being, Traffic Obstruction, And Discomfort Due Tointeractions With Beggars, Necessitating Targeted Interventions From Stakeholders To Ensuresafety On Sidewalks For All Pedestrians. Long-Term Interventions Like Economic Empowermentprograms, Enacting Comprehensive Anti-Begging Legislation, And Integrating Various Elementssuch As Sidewalks, Urban Design Principles, And Road Safety Measures Into A Unified Strategy Arehighly Recommended To Improve Sidewalk Safety And Overall Urban Mobility.
The Impact Of Street Begging On The Movement And Safety Of Pedestrians: The Case Of Megenagna, Addis Ababa
Keywords: Street begging, Safety, Pedestrian, Megenagna, Addis Ababa; Street Begging, Safety, Pedestrian, Megenagna, Addis Ababa